Violence as a research object and intervention in the health field: an analysis from the production of the Research Group on Gender, Health and Nursingi ;** - Oliveira, Rebeca Nunes Guedes de; Fonseca, Rosa Maria Godoy Serpa da (Revista da Escola de Enfermagem da USP, 2014)
The study aimed to describe how violence is revealed in the production of the Research Group on Gender, Health and Nursing. This is a historical research of qualitative approach, which evaluated the production of the Research Group, through content analysis. The results show gender as a central category in determining violence and health practices. This aspect determines limitations on professional practices of coping, such as the invisibility of the problem. The female autonomy, the use of alcohol and drugs and social vulnerability play an important relation with the phenomenon and the bond is revealed as potentiality of health practices to address the problem. Conclusion: The gender perspective in nursing research is an innovative field and counter-hegemonic, a possibility to assume a meaning of praxis by transforming potential of understanding and modes of intervention in the phenomenon of gender violence.